2013
DOI: 10.1371/journal.pbio.1001581
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Basis for IκB Kinase 2 Activation Via Oligomerization-Dependent Trans Auto-Phosphorylation

Abstract: Conformational change in human IKK2 permits dimers to form higher-order oligomers that support interaction between kinase domains and promote activation through trans auto-phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(156 citation statements)
references
References 39 publications
8
143
0
Order By: Relevance
“…In some cases, as exemplified by ASK2, the MAP3Ks themselves may lose their catalytic activity and become obligate dimerization partners that enhance the activation of other related MAP3Ks (38,39). MAP3K full activation also requires activation loop autophosphorylation, presumably in trans, through a transient tetrameric complex (similar to the IB kinases [IKKs]) (40,41). This phosphorylation of MAP3Ks increases and stabilizes their activity, removing the requirement of a dimeric state for substrate phosphorylation.…”
Section: Figmentioning
confidence: 99%
“…In some cases, as exemplified by ASK2, the MAP3Ks themselves may lose their catalytic activity and become obligate dimerization partners that enhance the activation of other related MAP3Ks (38,39). MAP3K full activation also requires activation loop autophosphorylation, presumably in trans, through a transient tetrameric complex (similar to the IB kinases [IKKs]) (40,41). This phosphorylation of MAP3Ks increases and stabilizes their activity, removing the requirement of a dimeric state for substrate phosphorylation.…”
Section: Figmentioning
confidence: 99%
“…However, the F305A NEMO mutation, which abolishes NEMO binding to both linear and Lys63-linked chains almost completely (24), strongly suppressed IL-1␤-induced NF-B activation, confirming the importance of ubiquitin binding by NEMO for NF-B activation. These results suggested that IKK2, a crucial kinase within the IKK complex that phosphorylates IB␣, homodimerizes via its kinase domain (KD), leading to activation of IKK via trans autophosphorylation (30). We examined the involvement of KD homodimerization of IKK2 in the activation of IKK provoked by linearly ubiquitinated NEMO.…”
Section: Ikk Is Effectively Activated By Linear Polyubiquitin Conjugamentioning
confidence: 99%
“…We examined the involvement of KD homodimerization of IKK2 in the activation of IKK provoked by linearly ubiquitinated NEMO. Val229, His232, Tyr294, Gly295, and Pro296 of human IKK2 are involved in the KD-KD interaction of IKK2 (30). Therefore, we mutated Val229 and His232 to Ala (V229A/H232A); in another construct, Tyr294, Gly295, and Pro296 were mutated to Leu, Lys, and Gln, respectively, the corresponding amino acids in IKK1 (Y294L/G295K/P296Q) (30).…”
Section: Ikk Is Effectively Activated By Linear Polyubiquitin Conjugamentioning
confidence: 99%
“…In general, phosphorylation of kinases is mediated either by trans-autophosphorylation or by upstream kinases [ 18 ]. The crystal structural analyses of human IKK2 revealed that homotypic interaction of the IKK2 kinase domain is crucial for IKK2 activation [ 19 ]. Moreover, NEMO possesses the ubiquitin binding activity that prefers linear di-ubiquitin, and NEMO's ubiquitin binding activity is critical for IKK activation [ 20 ].…”
Section: Mechanism Underlying Linear Ubiquitin Chain-mediated Nf-κb Amentioning
confidence: 99%